Preparation and Characterization of Organic/Inorganic Composite UV Filter Microcapsules by Sol-Gel Method - Pey-Shiuan Wu; Chia-Hui Lin; Yi-Ching Kuo; Chih-Chien Lin (Advances in Materials Science and Engineering)
Octyl methoxycinnamate and butyl methoxydibenzoylmethane are organic UV filters with poor photostability and will become photoallergy or phototoxic substance when exposed to ultraviolet radiation. The organic UV filters coated by microcapsules can reduce the photodegradation and avoid direct contact with the skin. Through microencapsulation, the application of UV filters in cosmetics becomes more effective and safer. This study first used the sol-gel method to create organic/inorganic composite UV filter microcapsules. We used sodium alginate as a shell material of the microcapsule to encapsulate UV filters. CaCO3 and tetraethyl orthosilicate (TEOS) were used as cross-linking agents, and sorbitan monooleate (Span 80) and polyoxyethylenesorbitan monooleate (Tween 80) were used as emulsifiers in the interfacial polymerization method for preparation. The results indicated that the microcapsules with 3 g of CaCO3 cross-linking agents had a similar particle size and better entrapment efficiency. The average sizes were 61.0 ± 4.9 μm and 48.6 ± 4.7 μm, and entrapment efficiencies were 75.3 ± 1.9% and 74.8 ± 1.7% for octyl methoxycinnamate and butyl methoxydibenzoylmethane, respectively. Utilizing sodium alginate as a cross-linking agent is better than TEOS due to the higher calcium content. In vitro transdermal delivery analysis showed that the release rate became steady.